Detection and quantification of 56 new psychoactive substances in whole blood and urine by LC–MS/MS. (May 2015) - Ambach, Lars; Hernández Redondo, Ana; König, Stefan; Angerer, Verena; Schürch, Stefan; Weinmann, Wolfgang
Background: New psychoactive substances (NPS) have become increasingly prevalent and are sold in internet shops as 'bath salts' or 'research chemicals' and comprehensive bioanalytical methods are needed for their detection.Methodology: We developed and validated a method using LC and MS/MS to quantify 56 NPS in blood and urine, including amphetamine derivatives, 2C compounds, aminoindanes, cathinones, piperazines, tryptamines, dissociatives and others. Instrumentation included a Synergi Polar-RP column (Phenomenex) and a 3200 QTrap mass spectrometer (AB Sciex). Run time was 20 min.Conclusion: A novel method is presented for the unambiguous identification and quantification of 56 NPS in blood and urine samples in clinical and forensic cases, e.g., intoxications or driving under the influence of drugs.